Delayed, deferred and dropped out: geographies of Filipino-Canadian high school students. Issue 2 (4th March 2017) - Farrales, May
Abstract : Models representing the assimilation of post-Second World War immigrants to North America use the academic achievement of children of first-generation immigrants as a benchmark of social mobility. Filipino youths in Canada fall short of this benchmark – they neither meet nor exceed their parents' academic achievements. While concern with outcomes is a useful starting point, I suggest that there is a need to interrogate how and where students are produced as different. To do this, I attend to the geographies in the narratives of youths gathered from Filipino high school students in Vancouver (unceded Coast Salish Territories). I examine how they negotiate the spaces of transnational migration, their lives as students and spaces where their educational trajectories are deferred and delayed. I argue that the geographies of transnational migration and family should be held together with spaces of the school and education when considering academic outcomes.